Personalized Adaptive Gamification and Learning Styles in Digital and Mobile Learning Environments: A Systematic Review - Tomaylla-Quispe, Ygnacio; Gutierrez-Aguilar, Olger; Chicana-Huanca, Sandra; Pérez-Postigo, Gerber (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study examines how personalized gamification relates to learning styles by identifying theoretical models, gamification approaches, and empirical evidence in education. A PRISMAbased systematic review was conducted across Scopus, Web of Science, and ScienceDirect, with an additional open-access screening phase. Thirty-four empirical studies from 2015–2025 were analyzed. The Felder-Silverman (FSLMS) model is the most frequently applied, followed by multiple intelligences (MI), Kolb, VARK, and cognitive-style frameworks. Gamification approaches include game-based learning, points–badges–leaderboards, customized and adaptive designs, hybrid structures, and technology-integrated systems, though some lack theoretical grounding. Experimental and quasi-experimental designs predominate, often relying on learning-style and perception questionnaires. Findings highlight five trends: personalized gamification increases motivation; learner profiles align with different game-element preferences; adaptive systems enhance attention and performance; learning styles influence satisfaction and engagement; and some cognitive profiles show neutral effects. Overall, evidence indicates a clear shift toward hybrid and adaptive personalized gamification supported by digital and mobile learning environments.